Compatibility of grafting in the melon cv. bônus No. 2, and effects on production - Braz, L. T. [UNESP]; Ito, L. A. [UNESP]; Charlo, H. C O [UNESP]; Castoldi, R. [UNESP] (My University, 2008)
Twelve rootstocks were evaluated: 1) pumpkin 'Big Power' (Cucurbita ntoschata); 2) pumpkin 'Seca' (Cucurbita moschata); 3) bottle gourd 'Longa' (Lagenaria siceraria); 4) 'Cachi' (Lagenaria siceraria); 5) bottle gourd 'Marimba' (Lagenaria siceraria); 6) 'Mogango' (Cucurbita maxima); 7) pumpkin 'Kirameki' (Cucurbita moschata); 8) pumpkin 'Caravela' (Cucurbita moschata); 9) pumpkin 'Shelper' (Cucurbita moschata); 10) 'Gherkin' (Cucumis anguria); 11) 'Loofah' (Luffa cylindrica); and 12) pumpkin 'Goianinha' (Cucurbita moschata) with respect to compatibility with melon yield, and the production and quality of fruits from cv. Bônus No. 2, non-grafted and grafted with 9 of these rootstocks (1, 2, 4, 5, 6, 7, 9, 10 and 11). The bottle gourd 'Marimba' provided the highest percentage of grafting success between the vine and rootstock. The rootstocks 1, 2, 3, 4 and 7 did not differ from bottle gourd 'Marimba', therefore also indicating good compatibility with the melon cv. Bônus No. 2. For height of the plants, it was shown in the first evaluation that rootstock 5 produced a greater height of the plant, differing only from rootstocks 7, 8, 9, 10 and 11 and non-grafted cv. Bônus No. 2. In the second evaluation, 'Big Power' showed the greatest value for height of the plant, differing only from combinations with 'Cachi', 'Mogango', 'Shelper' and 'Loofah'. With regard to number of leaves, in the first evaluation rootstocks 3, 4 and 6 had the greatest number of leaves, but in the second 4, 9 and 11 had the greatest. For dry weight of the stem, the greatest value was obtained with 'Mogango' in the first evaluation and with 'Big Power' in the second. For leaf area of the plants, a difference was found among the treatments only in the first evaluation, where the combination with bottle gourd 'Longa' showed a greater leaf area, but did not differ from the combinations with rootstocks 1, 4, 5 and 6. Differences were demonstrated among the treatments only for the transverse diameter of the fruit, where the combination with rootstock bottle gourd 'Marimba' showed the greatest value, differing only from the combination with 'Gherkin'. There were no significant differences for the mean longitudinal diameter, pulp thickness and total soluble solids among the treatments studied.
Keywords: Cucumis melo; Didymella bryoniae; Production; Rootstocks; Citrullus colocynthis; Cucumis; Cucumis anguria; Cucurbita; Cucurbita maxima; Cucurbita moschata; Lagenaria siceraria; Luffa; Luffa aegyptiaca